If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20m + -4 = 56 Reorder the terms: -4 + 20m = 56 Solving -4 + 20m = 56 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 20m = 56 + 4 Combine like terms: -4 + 4 = 0 0 + 20m = 56 + 4 20m = 56 + 4 Combine like terms: 56 + 4 = 60 20m = 60 Divide each side by '20'. m = 3 Simplifying m = 3
| 7(t-6)+8t=5(3t+3)-11 | | 15+5x=30x | | (x*.05)+1=20 | | 7(-3x+10)=-119 | | 8r^2-20r-12=0 | | 15t^2+8t+1=0 | | 11+8q=15+7q | | 2/5-2/3 | | 2z=5x-3y | | 2(a-4)=4a-(2a+9) | | -4-4-4= | | -7.8-4x-1.6-2x=-5x-0.2 | | 5x+25=5y+15 | | 2-1/2w=-7/6 | | 144=3(3x+9) | | 6(1-4n)=78 | | 7x-4=10x-1 | | 2a+3+a=a | | 2-1/2w=7/6 | | 2x^2-10x-3=(x-3)(x-3) | | .05x+1=20 | | j=3 | | -4x+4=5x-14 | | 27(-4)-9y=-9x^2 | | 3xn+4=4xn+1 | | 31-5*25/4 | | -x=-3x+2 | | 2a+3=a | | 6y-3-5y=0 | | 10.3+16.6y=-3(-6y-3.3) | | 2-1/3x=-5/6 | | 6+4i+3i=17-16i-2i |